1985
DOI: 10.1073/pnas.82.12.3964
|View full text |Cite
|
Sign up to set email alerts
|

Purification, induction, and distribution of placental glutathione transferase: a new marker enzyme for preneoplastic cells in the rat chemical hepatocarcinogenesis.

Abstract: A polypeptide of Mr 26,000 and pI 6.7 that was markedly increased in rat livers bearing hyperplastic nodules (HNs) induced by chemical carcinogens was identified immunochemically as the subunit of neutral glutathione (GSH) transferase (GSHTase; RX:glutathione R-transferase, EC 2.5.1.18; also called GSH S-transferase) purified from placenta (GSHTase-P) and was demonstrated immunohistochemically to be localized in preneoplastic foci and HNs. In the present study, GSHTase-P has been purified from the HN-bearing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
246
2
7

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 472 publications
(267 citation statements)
references
References 21 publications
12
246
2
7
Order By: Relevance
“…Previous reports showed that the tumor marker GST-P was markedly expressed and albumin was slightly decreased during hepatocarcinogenesis. 13,14) Under our conditions, these changes were reproduced and the induction of Hdac9 expression was also observed. These results indicated that Hdac9 was expressed during hepatocarcinogenesis.…”
Section: Expression Of the Hdac Family During Hepatocarcinogenesissupporting
confidence: 51%
“…Previous reports showed that the tumor marker GST-P was markedly expressed and albumin was slightly decreased during hepatocarcinogenesis. 13,14) Under our conditions, these changes were reproduced and the induction of Hdac9 expression was also observed. These results indicated that Hdac9 was expressed during hepatocarcinogenesis.…”
Section: Expression Of the Hdac Family During Hepatocarcinogenesissupporting
confidence: 51%
“…To analyze lipid peroxidation and oxidative DNA damage, immunohistochemical staining for 4-hydroxy-2-nonenal (4-HNE) adducts and 8-hydroxydeoxyguanosine (8-OHdG) was performed using the avidin-biotin-peroxidase complex (ABC) method as previously described 33 with a Vectastain elite ABC kit (Vector Laboratories, Burlingame, CA). Briefly, liver sections 5 m thick were deparaffinized with xylene and alcohol series.…”
Section: Analysis Of Lipid Peroxidation and Oxidative Dna Damagementioning
confidence: 99%
“…These liver slices were fixed in ice-cold acetone for the immunohistochemical examination of the GST-P positive foci. The avidin-biotinperoxidase complex method (Vectastain ABC kit, Vector Lab., Burlingame, USA; Hsu et al, 1981) was used to demonstrate the GST-P positive liver foci, a putative preneoplastic lesion (Sato et al, 1984). An immunohistochemical analysis was carried out with sequential treatments of rabbit anti-rat GST-P (MBL Co., Nagoya, Japan) as a primary antibody, goat anti-rabbit IgG antibody as a secondary antibody, and the peroxidase-antiperoxidase complex.…”
Section: Animals and Dietmentioning
confidence: 99%